PERTANGGUNGJAWABAN PIDANA TERHADAP TINDAK PIDANA ILLEGAL MINING BAGI PERSEORANGAN : STUDI KASUS PUTUSAN NO. 146/PID.SUS/2020/PN SMN - Eko Djoko Widiyatno; Suryawan Raharjo; Eko Nurharyanto (Kajian Hukum, 2025)
Criminal Responsibility Against Illegal Mining for Individuals (Decision Case Study No. 146/Pid.Sus/2020/PN SMN) with the objectives: (1) To find out the law enforcement process against illegal mining crimes for individual that carry out mining without permission. (2) To find out criminal responsibility for illegal mining for individual that carry out mining without a permit, especially in the case study of decision No. 146/PID. SUS/2020/PN SMN. As well as to examine a decision number 146/Pid.Sus/2020/PN SMN and analyze a criminal act of illegal mining and accountability for mining without a permit. The research method uses a statute approach and a conceptual approach, where the statutory approach examines, examines legal products and study case approach, while the conceptual approach examines legal concepts. And this type of research uses normative research. The author conducts an analysis related to a decision that will be examined, namely regarding criminal responsibility for perpetrators of illegal mining crimes for individuals. Clearly different forms of accountability for individuals with companies. The results of the study discuss law enforcement and criminal responsibility related to decision no. 146/Pid.Sus/2020/PN Smn which is principally related to law enforcement in repressive and preventive ways. Meanwhile, criminal responsibility is carried out by obtaining the facts at trial and the judge's considerations. Criminal liability for illegal sand miners will be subject to punishment according to the actions they have committed.